A systematic review of interventions to improve post-secondary educational outcomes among foster care alumni. (August 2017) - Randolph, Karen A.; Thompson, Heather
Abstract: In their transition to adulthood, youth who have aged out of foster care struggle in a variety of areas. One area of concern is achieving success in post-secondary education. In response, universities and community colleges around the country offer support programs for these youth, in order to assist them in gaining a college education. The purpose of this study was to utilize a systematic review process to uncover the current status of what is known about campus support programs for foster care alumni in two areas—student views of their program experiences and outcomes of interventions to improve post-secondary educational success. We adapted the Participants, Interventions, Comparison groups, Outcomes, and Study designs (PICOS) model in conducting the systematic review. A search of six electronic databases and other gray literature sources yielded seven articles. Results revealed valuable insight from students regarding the ways in which program implementation was beneficial, and highlighted important strategies future programs should consider. Further, findings of outcome studies are favorable. However, additional outcome evaluations are needed in order to validate and confirm their impact. Highlights: There has been substantial increase in campus-based support programs for foster care alumni within academic institutions. This systematic review examines studies about students' view of their program experiences as well as student outcomes. Findings highlight student views of valuable services and indicate that the impact on student outcomes is promising. Recommendations for future program development and evaluation are included.